2021
DOI: 10.1289/ehp7305
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Lung Structure and Function after Long-Term Exposure to an Atmospheric Carbon Dioxide Level Predicted by Climate Change Modeling

Abstract: BACKGROUND: Climate change models predict that atmospheric carbon dioxide [CO 2 ] levels will be between 700 and 900 ppm within the next 80 y. Despite this, the direct physiological effects of exposure to slightly elevated atmospheric CO 2 (as compared with ∼ 410 ppm experienced today), especially when exposures extend from preconception to adulthood, have not been thoroughly studied. OBJECTIVES: In this study we aimed to assess the respiratory structure and function effects of long-term exposure to 890 ppm CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…Carbon dioxide is produced by the combustion of fossil fuels or forest fires [5,18]. One recent study explored the effect of carbon dioxide alone in mice and established that it leads to a range of respiratory impairments such as higher elastance in the lung and lower lung compliance [77]. This study also showed that during early life when the lungs are still growing and under development, they are most sensitive to carbon dioxide which might lead to alveolar destruction and other lung structures [77].…”
Section: Carbon Dioxidementioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dioxide is produced by the combustion of fossil fuels or forest fires [5,18]. One recent study explored the effect of carbon dioxide alone in mice and established that it leads to a range of respiratory impairments such as higher elastance in the lung and lower lung compliance [77]. This study also showed that during early life when the lungs are still growing and under development, they are most sensitive to carbon dioxide which might lead to alveolar destruction and other lung structures [77].…”
Section: Carbon Dioxidementioning
confidence: 99%
“…One recent study explored the effect of carbon dioxide alone in mice and established that it leads to a range of respiratory impairments such as higher elastance in the lung and lower lung compliance [77]. This study also showed that during early life when the lungs are still growing and under development, they are most sensitive to carbon dioxide which might lead to alveolar destruction and other lung structures [77]. Combined with exposure to organic dust, low levels of carbon dioxide can alter immune responses leading to more airway inflammation and induction of pro-inflammatory cytokines [78,79].…”
Section: Carbon Dioxidementioning
confidence: 99%
“…The environmental exposures have been detailed in (Larcombe et al 2021). In brief, adult female and male mice were randomly assigned to one of two experimental conditions; control mice (Con) were housed at 465 ± 27 ppm atmospheric CO 2 (standard housing atmospheric conditions) and the experimental group (CO 2 ) were housed at 889 ± 123 ppm atmospheric CO 2 (900 ppm was aimed at for as the predicted atmospheric conditions, exposure averaged to 889 ppm for the duration of the experiment, see Larcombe et al (2021) for more details). Both groups were allowed to acclimatise to their assigned atmospheric condition for a period of 2 weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…We have recently provided the first evidence, to our knowledge, that exposure of mice to 890 ppm CO 2 from pre‐pregnancy and early life through to 3 months of age elicits changes in respiratory structure and function with haematological measures indicative of borderline respiratory acidosis (Larcombe et al . 2021). The respiratory changes were observed only in female offspring and were possibly driven by exposure in early life.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study exposing pregnant mice and their newborn to concentrations of just below 900 ppm found higher tissue elastance, longer chord length and lower lung compliance in the offspring. 19 The IPCC Shared Economic Pathway 6 will approach these CO 2 concentrations and Shared Socioeconomic Pathway 8.5 will pass them by the end of this century. 20 Environmental degradation drives poorer child health in Africa.…”
Section: Environmental Damage and Its Effects On Child Healthmentioning
confidence: 99%